Maturity Stages of Pink Shrimp Farfantepenaeus notialis (Penaeidae) in the Colombian Caribbean - Daniel Giovanny Pérez Ferro; Jorge Enrique Paramo Granados (Acta Biológica Colombiana, 2014)
The pink shrimp Farfantepenaeus notialis is one resource of great socioeconomic importance in the Caribbean region. However, this species has been overexploited in the last decades and there is a lack of biological and fishery information. For such reason, the objective of the present study is to determine and characterize the maturity stages a macroscopic and microscopic level of the pink shrimp (F. notialis) as input for its management. The samples were taking from June of 2012 and May 2013, on board shrimp commercial vessels in the Colombian Caribbean. The females of F. notialiswere identified and preserved for the histologic analysis and some gonads were fixed. Data of size, weight and sex were taken. The gonadal stages were determined from the morphology and coloration of gonad and to microscopic determination were carried out histologic cut from samples of thirty gonads from all stages. A total of 3019 females were obtained from F. notialis, to which five stages of gonadal development